Risk factors associated with the recurrence of diabetic foot ulcers: A meta-analysis. - Chunmei Lin; Jianqing Tian; Zhijun Zhang; Caiyu Zheng; Jinhao Liu (PLoS ONE)
Aims Diabetic foot ulcers have caused significant medical, economic and social consequences for patients, families and society. With appropriate treatment, many diabetic foot ulcers can heal, temporarily avoiding possible amputation. Unfortunately, even if foot ulcers subside, recurrence is still common. The recurrence of ulcer has brought another physical and psychological trauma to diabetic foot patients who yearn for a better life. Therefore, it may be more useful to evaluate the factors associated with ulcer recurrence in diabetic foot ulcer patients. Methods The PubMed, Web of Science, Embase and China National Knowledge Infrastructure databases were comprehensively searched for prospective or retrospective studies published up to February 1, 2024. All English or Chinese language studies on diabetic foot ulcer patients who experience recurrence were included, and RevMan 5.3 software was used to analyze the data. Results A total of 22 studies meeting the eligibility criteria were ultimately included in this meta-analysis. 1861 of 5252 diabetic foot ulcer patients experienced recurrence during follow-up. The following variables were associated with an increased risk of ulcer recurrence: male (OR = 1.26, 95% CI = 1.10 ~ 1.44, P = 0.0009), smoking history (OR = 1.18, 95% CI = 1.04 ~ 1.35, P = 0.01), living alone (OR = 1.86, 95% CI = 1.21 ~ 2.86, P = 0.004), plantar ulcers (OR = 2.44, 95% CI = 1.41 ~ 4.23, P = 0.001), diabetic retinopathy (OR = 1.59, 95% CI = 1.35 ~ 1.88, P < 0.00001), diabetic nephropathy (OR = 1.37, 95% CI = 1.12 ~ 1.68, P = 0.002), diabetic peripheral neuropathy (OR = 1.78, 95% CI = 1.45 ~ 2.19, P < 0.00001), foot deformity (OR = 2.51, 95% CI = 1.85 ~ 3.40 P < 0.00001) and peripheral arterial disease (OR = 3.10, 95% CI = 2.43 ~ 3.95 P < 0.00001). However, hypertension (OR = 1.16, 95% CI = 0.96 ~ 1.40, P = 0.13) and body mass index (MD = 0.20, 95% CI = -0.12 ~ 0.53, P = 0.22) were not associated with diabetic foot ulcer recurrence. Conclusions Our meta-analysis identified the following important risk factors for diabetic foot ulcer recurrence: male sex, smoking history, living alone, plantar ulcer, diabetic retinopathy, diabetic nephropathy, diabetic peripheral neuropathy, foot deformity, and peripheral arterial disease. Understanding these factors and their impact on ulcer recurrence is crucial for multidisciplinary teams to develop management and treatment plans for diabetic foot ulcer patients.